The Model of the Formation of the Legal Competence of the Students In the Study of Legal and Historical Subjects - MUSSABEKOVA, Nursulun; OLZHABAYEV, Bulat; ZHAKISHEVA, Anara; AKHMADIYEVA, Aigul; BATAY, Amangul; SAKENOV, Janat (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The problem of the development of a model of the formation of the legal competence of the students in the study of legal and historical subjects is studied in this paper. The essence of the concept ‘The legal competence of the students’ is studied herein to justify the methodology for the development of the model of the formation of the legal competence of the students in the study of legal and historical disciplines. The content-related components of the legal competence of students were justified in the course of the development of the model of the formation of the legal competence of the students in the study of legal and historical subjects. The role of the legal and historical subjects in the process of the formation of the legal competence of the students was described. The model of the formation of the legal competence of the students in the study of the legal and historical subjects, including the criteria, the indicators, and the levels of the formation of the legal competence of students was developed. The model of the formation of the legal competence of the students in the study of the legal and historical disciplines is recommended for use in the development of university educational programs.